CPA Switches and Associated Market Reactions. - Fried, Dov; Schiff, Allen (The Accounting Review, 1981)
ABSTRACT: In 1978, the Securities and Exchange Commission issued its final requirements concerning the disclosure requirements of companies that change their auditors. Along with a filing requirement for an auditor change, companies were also required to enumerate and describe disagreements they may have had with their CPAs on accounting and auditing issues in the 18 months prior to the change. To provide evidence on the existence and degree of market impact of these disclosure requirements, the behavior of stock prices of a sample of companies that switched auditors and a matched pair of control companies that did not were analyzed. Results of the study appear to be inconsistent with the SEC requirement for companies to enumerate and describe disagreements with their auditors. For the general event of auditor changes, there seems to be negative market reaction around the time of the switch; however, there is some difficulty in interpreting the motivation for this reaction.